CATION SITE OCCUPANCY IN SPINEL FERRITES STUDIED BY X-RAY MAGNETIC CIRCULAR DICHROISM: DEVELOPING A METHOD FOR MINERALOGISTS - Pattrick R.A.D.; van Der Laan G.; Henderson Michael B.C.M.B.; Kuiper P.; Dudzik E.; Vaughan D.J. (My University, 2002)
X-ray magnetic circular dichroism (XMCD) is an element-, site- and symmetry-selective spectroscopic technique that has the potential to provide quantitative information on site occupancies in ferri- and ferro-magnetic minerals. XMCD spectra derived from the Fe L(2,3) absorption edge of a series of synthetic spinel ferrites and natural magnetite were collected using synchrotron radiation and a 0.6 Tesla 'flipper' magnet. These spectra were used to assess their potential value to mineralogical investigations. By comparison with theoretical spectra, the site occupancies of the cations have been calculated and compared to previous studies using other techniques. The spectra of the Co, Ni, Zn and Mg ferrite spinels show considerable variation, reflecting differences in site occupancies. Although the cation ratios derived from the XMCD spectra are broadly similar to previous work, there are significant differences especially in the amount of octahedral Fe(2+) present. Incomplete inversion is recognised in all the spinels analysed and the affinity of Co, Ni and Mg for the octahedral site and Zn for the tetrahedral site is confirmed; the preference of Co over Ni for tetrahedral sites is also revealed. XMCD spectra proved relatively straightforward to analyse but further refinement of the quantitative calculations is needed and detailed comparison with the information derived from other methods, especially Mossbauer spectroscopy.